Added clinical use of trabecular bone score to BMD for major osteoporotic fracture prediction in older Chinese people: the Mr. OS and Ms. OS cohort study in Hong Kong. Issue 1 (January 2017) - Su, Y.; Leung, J.; Hans, D.; Aubry-Rozier, B.; Kwok, T.
Abstract Summary The thresholds of trabecular bone score (TBS) require validation for clinical application in older Chinese people. The lower threshold of TBS significantly improved the accuracy of prediction by bone mineral density-based osteoporosis status for major osteoporotic fracture in older Chinese men. Introduction Trabecular bone score (TBS) is a relatively new indicator of skeletal fragility. Its clinical application warrants further investigations. Our aim was to validate and recommend practical thresholds of TBS for fracture prediction in older Chinese people. Methods Older men and women in Mr. and Ms. Os (Hong Kong) study were followed up for an average of 9.94 ± 2.77 and 8.82 ± 1.49 years, respectively. Major osteoporotic fracture (MOF) risks of TBS category in each BMD category (normal, osteopenia, or osteoporosis) were compared using Poisson regression model. The improved fracture risk prediction power was evaluated by the sensitivity, the specificity, the area under the receiver-operating characteristic curve (AUC), and the net reclassification improvement index (NRI). Results MOF incidence gradually increased with the increased risk categories of bone mineral density (BMD) and tertiles of TBS both in men and women. Compared with the lowest risk category, the rate ratios (RR, 95 % CI) of MOF for osteoporosis with the lowest TBS was 9.66 (4.19–22.26) and 6.24 (1.53–25.42) in men and women, respectively. The fracture risk for osteopenic men with the lowest TBS was significantly higher than that for normal men, with RR (95 % CI) of 4.68 (2.11–10.41). The predictive power of osteoporosis alone was significantly improved by TBS in men [mean AUC (95 % CI) rose from 0.604 (0.562–0.646) to 0.666 (0.623–0.710) and sensitivity rose from 32.5 to 64.3 %]. The improvement in predictive power was not significant in older women. Conclusions TBS in combination with BMD can predict MOF more reliably in older men than by BMD alone.